The Effect of Direct and Indirect Monitoring on Generosity Among Preschoolers - Fujii, Takayuki (Sci Rep, 2015)
The purpose of this study is to examine the effect of direct and indirect monitoring on generosity among five-year-old preschoolers and to reveal the primary motivation for their generosity. Forty-two preschoolers completed one-shot dictator games in Condition 1 while being monitored by the experimenter (the direct monitoring condition). In Condition 2, an image of staring eyes was displayed on the computer monitor (the indirect monitoring condition). In Condition 3, the computer monitor showed a picture of flowers (the non-monitoring condition). The results showed that while there was no difference between the mean levels of allocation in the indirect and non-monitoring conditions, the mean level of allocation in the direct monitoring condition was significantly higher than in the non-monitoring condition. These results showed that five-year-old preschoolers concerned with being monitored by, and receiving direct responses from, others tend to be more generous.